Overrated energy storage performances of dielectrics seriously affected by fringing effect and parasitic capacitance - Song Ding; Jiangheng Jia; Bo Xu; Zhizhan Dai; Yiwei Wang; Shengchun Shen; Yuewei Yin; Xiaoguang Li (Nature Communications)
Abstract Dielectric capacitors are vital for modern power and electronic systems, and accurate assessment of their dielectric properties is paramount. However, in many prevailing reports, the fringing effect near electrodes and parasitic capacitance in the test circuit were often neglected, leading to overrated dielectric performances. Here, the serious impacts of the fringing effect and parasitic capacitance are investigated both experimentally and theoretically on different dielectrics including Al2O3, SrTiO3, etc. The deviations are more critical for the measurements of capacitors using asymmetric electrodes with different areas and for dielectrics with a lower dielectric constant, and differences tested in silicone oil and air environments should be noticed. A method to calibrate the parasitic capacitance of the test circuit is also raised for ensuring the accuracy of measured dielectric performances. Enlarging the electrode diameter and/or thinning the sample can reduce the above deviations, and thus a general standard of setting capacitor configurations is proposed for the measurement validity. Our study clearly demonstrates that it is necessary to mitigate the fringing effect and subtract the parasitic capacitance to solve the problem on overrated dielectric performances, which is very important for the development of the dielectric research in a healthy and orderly way.